2013
DOI: 10.1242/jcs.110031
|View full text |Cite
|
Sign up to set email alerts
|

A non-catalytic role for inositol 1,3,4,5,6-pentakisphosphate 2-kinase in the synthesis of ribosomal RNA

Abstract: SummaryFundamental to the life and destiny of every cell is the regulation of protein synthesis through ribosome biogenesis, which begins in the nucleolus with the production of ribosomal RNA (rRNA). Nucleolar organization is a highly dynamic and tightly regulated process; the structural factors that direct nucleolar assembly and disassembly are just as important in controlling rRNA synthesis as are the catalytic activities that synthesize rRNA. Here, we report that a signaling enzyme, inositol 1,3,4,5,6-penta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…2F) and the percentage of metastases to liver (Fig. 2G), the most common site of metastasis for The inositol polyphosphate kinases, including IP6Ks, have both catalytic activity-dependent and -independent functions (1,5,11,27,28). To examine whether the oncogenic actions of IP6K2 depend on its catalytic activity, we established rescue cell lines by retroviral expression of wild-type (WT-R) or kinase-dead K222A IP6K2 (29) (KD-R) in IP6K2 −/− cells.…”
Section: Significancementioning
confidence: 99%
“…2F) and the percentage of metastases to liver (Fig. 2G), the most common site of metastasis for The inositol polyphosphate kinases, including IP6Ks, have both catalytic activity-dependent and -independent functions (1,5,11,27,28). To examine whether the oncogenic actions of IP6K2 depend on its catalytic activity, we established rescue cell lines by retroviral expression of wild-type (WT-R) or kinase-dead K222A IP6K2 (29) (KD-R) in IP6K2 −/− cells.…”
Section: Significancementioning
confidence: 99%
“…A reported study suggested that human IP 5 2-K presents a different putative Zinc binding motif possibly related with the enzyme capacity to translocate to the nucleus [2]. Moreover, mIP 5 2-K associates with several proteins involved in rRNA synthesis; but data of possible interacting regions are lacking [9]. Considering that the ipk1 gene deletion in plants does not present a dramatic effect while in mammals the embryo is not viable [30], this enzyme seems to present specific features and roles in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover IP 6 is the precursor of pyrophosphate inositol diphospho-inositol pentakisphosphate (IP 7 ) and bisdiphosphoinositol tetrakisphosphate (IP 8 ) [6], which are involved in apoptosis processes [7,8]. Very recently, IP 5 2-K has been shown to present a double functionality; apart from its kinase function it presents a structural role in the cell nucleolus, interacting with at least three proteins involved in the regulation of rRNA synthesis [9]. In concordance with the important functions ascribed to IP 5 2-K in mammals, disruption of its gene produces early lethality and non-viable murine embryos [10].…”
Section: Introductionmentioning
confidence: 99%
“…While nucleolin has not previously been identified as an IP-binding protein, co-localization of nucleolin with IPK1, the primary enzyme that produces IP 6 through phosphorylation of IP 5 , and phosphorylation of nucleolin by IP 7 link nucleolin with IP 6 metabolism and suggest that nucleolin may interact with IP 6 (15,(53)(54)(55). Western blot analysis using anti-nucleolin antibodies identified nucleolin as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 one of the proteins retained by IP 6 -biotin affinity capture ( Figure 4B).…”
Section: Synthesis Of Ipmentioning
confidence: 99%
“…We used a candidate protein approach to determine whether a likely IP 6 -binding protein was affinity captured by IP 6 -biotin. Nucleolar localization of the IP 5 kinase that produces IP 6 suggests a role for IP 6 in the nucleolus (15,53). When expressed in yeast, the human nucleolar protein nucleolin can be directly phosphorylated by the inositol pyrophosphate IP 7 (see supplemental figure S3B, (55)), which suggests a possible physical interaction with highly phosphorylated IPs such as IP 6 (54,55).…”
Section: And Nopp140mentioning
confidence: 99%